Two Kinds of Hydrogen Monomers Manifested in Plasma-Exposed Silicon - Vladimir V. Voronkov (Advances in Materials Science and Engineering)
In boron-doped silicon annealed in a plasma ambient (at 150°C), the reported hydrogen concentration profile and the hole profile cannot be simultaneously fitted assuming only one kind of in-diffusing hydrogen ions H+ of a definite parameter D+K (where D+ is the diffusivity of H+ and K is the equilibrium dissociation constant of the HB defect, the passivated boron). A good fit is possible only assuming two independent kinds of H+—one of a larger value of D+K and the other—of a smaller value. A concept of two independent atomic subsystems H(1) and H(2), each involving both positive and neutral charge states, is also useful to account for hydrogen pairing into dimers.